2010
DOI: 10.1038/nature08707
|View full text |Cite
|
Sign up to set email alerts
|

Dominant control of the South Asian monsoon by orographic insulation versus plateau heating

Abstract: The Tibetan plateau, like any landmass, emits energy into the atmosphere in the form of dry heat and water vapour, but its mean surface elevation is more than 5 km above sea level. This elevation is widely held to cause the plateau to serve as a heat source that drives the South Asian summer monsoon, potentially coupling uplift of the plateau to climate changes on geologic timescales. Observations of the present climate, however, do not clearly establish the Tibetan plateau as the dominant thermal forcing in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
542
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 801 publications
(576 citation statements)
references
References 31 publications
31
542
1
2
Order By: Relevance
“…Boos and Kuang [11], by removing the main body of the TP and retaining only the narrow terrain of the Himalayas in their numerical experiments, found that the simulated South Asian summer monsoon, precipitation and large-scale atmospheric circulation structures were similar to the simulated results with all topography retained. Thus they concluded that the dynamic barrier effect caused by the uplift of the Himalayas was much more important than the thermal effect of the TP for the formation and development of the South Asian summer monsoon.…”
Section: Effects Of Himalayan-tibetan Plateau Sub-regional Uplift Onmentioning
confidence: 87%
See 3 more Smart Citations
“…Boos and Kuang [11], by removing the main body of the TP and retaining only the narrow terrain of the Himalayas in their numerical experiments, found that the simulated South Asian summer monsoon, precipitation and large-scale atmospheric circulation structures were similar to the simulated results with all topography retained. Thus they concluded that the dynamic barrier effect caused by the uplift of the Himalayas was much more important than the thermal effect of the TP for the formation and development of the South Asian summer monsoon.…”
Section: Effects Of Himalayan-tibetan Plateau Sub-regional Uplift Onmentioning
confidence: 87%
“…This has led some scholars to speculate that to what extent the East Asian Monsoon should be regarded as monsoon [69]. Subsequently, the work by Boos and Kuang [11] was challenged. Wu et al [77] pointed out that though their numerical experiments removed the main body of the TP and retained only the Himalayas and adjacent narrow terrain, the surface sensible heat flux of the Himalayas was retained as well, To examine the effect of the uplift of southern TP…”
Section: Effects Of Himalayan-tibetan Plateau Sub-regional Uplift Onmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate models show that uplift of the Tibetan Plateau and the redistribution of land and sea, associated with the continentcontinent collision of India and Asia, caused continental aridification and intensification of the monsoons (Ramstein et al, 1997;Boos and Kuang, 2010). As a result, paleoenvironmental records have invariably associated Tibetan and Himalayan uplift with evidence for aridification north of the Tibetan Plateau and monsoon intensification to the south (e.g.…”
Section: General Geologymentioning
confidence: 99%